Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1177/1526924817699968
|View full text |Cite
|
Sign up to set email alerts
|

Transplant Professionals’ Perceptions of Long-Term Care Residents’ Candidacy for Kidney Transplantation

Abstract: This survey of a large number of KTx professionals suggests that there is presently no best practice consensus regarding offering KTx to patients living in LTC settings. Further research should include a broader range of KTx professionals and should also include a study of outcomes with KTx in this particular patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Moreover, the variation we observed may contribute to observed geographic and racial or ethnic disparities in access to kidney transplantation and downstream outcomes, 37 , 38 including where these disparities persist after controlling for patients’ comorbid conditions, including known contraindications to transplant. 39 Variation in local transplant center criteria and in clinical practice guidelines themselves 40 , 41 , 42 , 43 will also contribute to geographic variation in kidney transplant access, both independently and through their influence on the referral behaviors of nephrologists and their care teams. Notably, because our survey focuses on the earliest step on the pathway to transplant—the nephrologist’s prereferral assessment of the patient’s suitability for transplant—it may be that factors at work in other downstream steps (e.g., transplant center evaluation) could accentuate or mitigate associations between the referring nephrologists’ application of evaluation criteria and downstream patient waitlisting and transplant receipt outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the variation we observed may contribute to observed geographic and racial or ethnic disparities in access to kidney transplantation and downstream outcomes, 37 , 38 including where these disparities persist after controlling for patients’ comorbid conditions, including known contraindications to transplant. 39 Variation in local transplant center criteria and in clinical practice guidelines themselves 40 , 41 , 42 , 43 will also contribute to geographic variation in kidney transplant access, both independently and through their influence on the referral behaviors of nephrologists and their care teams. Notably, because our survey focuses on the earliest step on the pathway to transplant—the nephrologist’s prereferral assessment of the patient’s suitability for transplant—it may be that factors at work in other downstream steps (e.g., transplant center evaluation) could accentuate or mitigate associations between the referring nephrologists’ application of evaluation criteria and downstream patient waitlisting and transplant receipt outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although attempts have been made to standardize the kidney transplant evaluation with measures such as proposed prognostic indicators, expert guidelines‚ and multidisciplinary involvement on transplant committee teams, subjective input continues to play a role. There are several published qualitative studies that examine a nephrologist's perceptions and practices regarding transplant candidacy, [16][17][18] but quantitative data are sparse. Lenihan et al 19 used multivariate logistic regression to explore factors associated with waitlisting for transplant specifically in the elderly population and found that older age, coronary artery disease, and poor mobility adversely affected listing.…”
Section: Discussionmentioning
confidence: 99%